PRESERVING CULTURAL MEANING: STRATEGIES FOR TRANSLATING REALIA IN CROSS-CULTURAL COMMUNICATION (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
This article examines the translation of cultural realia in cross-cultural communication and the strategies used to preserve cultural meaning in the target language. Cultural realia refer to culture-specific lexical items that reflect traditions, institutions, food, and social practices, often without direct equivalents in other languages (Newmark, 1988). The study analyzes key translation strategies such as borrowing, calque, adaptation, generalization, explicitation, domestication, and foreignization (Venuti, 1995; Baker, 2011). The findings indicate that translation of cultural realia requires a flexible, context-dependent approach rather than a single universal method. Translators must balance cultural preservation and readability to ensure effective communication across cultures (Nord, 1997).